A study on fish composition in the Air Hitam River, Pekanbaru, Riau Province - Pulungan, Chaidir P.; ', Firdaus; ', Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The Air Hitam River was inhabit by numerous fish species, information on these fishhowever is almost none. To understand the composition of fish in that river, a study hasbeen conducted from February to March 2014. There were 3 sampling sites, in theupstream (S1), middle (S2) and downstream (S3) of the river. The fish was sampledusing several net types (mesh size 0.1 – 1.0 inch), electrofoshing and line fishing. Datawere then analyzed to find out the diversity (H’), evenness (E) and dominance (C)index. The fish sampled were identified based on Kottelat (2013). The fish speciespresent were consisted of 34 species (15 families). There were Notopterus notopterus,Cyclocheilichthys apogon, Desmopuntius gemellus, D. hexazona, Esomus metallicus,Hampala macrolepidota, Labiobarbus leptocheilus, Osteochillus vittatus, Parachelaoxygastroides, Rasbora argyrotaenia, R. einthovenii, R trilineata, Tynnichthyspolylepis, Trigonopoma gracile, Pterygoplichthys pardalis, Ompok rhadinurus,Pseudeutropius brachypopterus, P. moolenburghae, Mystus nigriceps,Hemirhamphodon pogonognathus, Poecilia reticulata, Monopterus javanensis,Pristolepis grooti, Oreochromis niloticus, Anabas testudineus, Helostoma temminckii,Belontia hasselti, Osphronemus goramy and Sphaerichthys osphromenoides,Trichopodus leerii, T. trichopterus, Trichopsis vittata, Channa lucius and C. striata.The most common fish was Pterygoplichthys pardalis that was present mainly in theS2. Trichopodus trichopterus and Trichopsis vittata were distributed evenly along theriver, as they were found in each sampling area (Fi 100%). In the Air Hitam River, thehighest H’ value (3. 671) and the highest E value (0.880) were in the upstream, whilethe highest C (0.476) was in the middle stream.Keyword: Freshwater fish composition, Air Hitam River, Pekanbaru, Riau